Complete remission in a patient with sinonasal squamous cell carcinoma receiving neoadjuvant tislelizumab plus chemotherapy: a case report - Chen, Fang; Zhang, Hongzheng; Li, Yonghe; Liang, Tingfeng; Zhang, Tao (Frontiers in Immunology, 2024)
Sinonasal squamous cell carcinoma (SNSCC) is the most common, high-aggressive sinonasal malignancies that have remained relatively stable poor outcomes over the past decade. As a first-line treatment for SNSCC, surgery plus adjuvant radiotherapy is recommended. However, complete surgical resection may not be appropriate due to the proximity of the nasal cavity and sinuses to key structures such as orbit or intracranial. Currently, immune checkpoint inhibitors (ICIs) have been established as one of the first-line therapies for many solid tumors with unresectable stage. However, evidence on the efficacy of ICIs in sinonasal malignancy is scarce and no ICIs are approved for use in SNSCC up to day. In this report, we report a case of a 64-year-old man with SNSCC treated by multi-protocol exploration. The patient achieved pathological complete response (pCR) after receiving two cycles of Docetaxel and cisplatin combined with tislelizumab. To the best of our knowledge, this is the first case of SNSCC treated with tislelizumab that achieved pCR. This case offers real-world evidence that chemotherapy plus immunotherapy is a promising treatment for SNSCC.